2016
DOI: 10.1002/rnc.3598
|View full text |Cite
|
Sign up to set email alerts
|

Event-triggeredHcontrol for a class of nonlinear networked control systems using novel integral inequalities

Abstract: Summary This paper is concerned with event‐triggered H∞ control for a class of nonlinear networked control systems. An event‐triggered transmission scheme is introduced to select ‘necessary’ sampled data packets to be transmitted so that precious communication resources can be saved significantly. Under the event‐triggered transmission scheme, the closed‐loop system is modeled as a system with an interval time‐varying delay. Two novel integral inequalities are established to provide a tight estimation on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(69 citation statements)
references
References 46 publications
0
68
0
1
Order By: Relevance
“…Currently, though the conditions of asymptotic stability for fractional-order system with constant timedelays have been established from the view of eigenvalues, the study of fractional-order system with time-varying delays is very difficult due to the complexity of fractional-order derivative, so, compared with the integer-order system [55,56], it is impossible to extend the results to the FOS with timedelays until now.…”
Section: Corollary 14 Given Positive Scalar Design Parameter Nonlimentioning
confidence: 99%
“…Currently, though the conditions of asymptotic stability for fractional-order system with constant timedelays have been established from the view of eigenvalues, the study of fractional-order system with time-varying delays is very difficult due to the complexity of fractional-order derivative, so, compared with the integer-order system [55,56], it is impossible to extend the results to the FOS with timedelays until now.…”
Section: Corollary 14 Given Positive Scalar Design Parameter Nonlimentioning
confidence: 99%
“…With the increasing popularity of networked cyber‐physical systems across all disciplines, it is important to efficiently manage the communication resource. To perform intermittent communication, there are two sampling schemes adopted in the literature . One is time‐triggered sampling, where agents transmit information to their neighbors depending on time.…”
Section: Introductionmentioning
confidence: 99%
“…The ETS is to transmit information only when the relative measurement error exceeds the certain boundary, where the boundary is obtained by input‐to‐state stability (ISS). Compared with the periodic sampling, the ETS has been verified to have significant advantages in decreasing the controller updates and alleviating the transmission burden of the communication network . Therefore, recent years have witnessed the extensive studies on the ETS of the COR for MASs in .…”
Section: Introductionmentioning
confidence: 99%
“…We note that for various behaviors, the stability has proven to be the most important one that has received considerable research attention. For example, if a neural network is given to solve some optimization problems, it is highly desirable for the neural network to have a unique globally stable equilibrium, and so, the stability analysis of CNNs has been an ever hot research topic resulting in enormous stability conditions reported in the literature, see e. g. [3,6,8,10,14,20,26,28,34,37,39,42,43,44,45,46].…”
Section: Introductionmentioning
confidence: 99%